Flash-Vacuum Expansion, a Low Cost and Energy-Efficient Alternative Process to Produce High-Quality Fruit Puree: Application to Physalis Peruviana - Arias, Claudia; Rodriguez, Pablo; Soto, Iris; Vaillant, Rowan; Cortés, Misael; Vaillant, Fabrice (SSRN, 2024)
Goldenberry has a great potential for the development of high-quality products due to its attractive sensory attributes, bioactive compounds, and health benefits. However, postharvest losses are high due to the lack of processing technologies that can both be adapted to rural conditions in producing countries to generate high-quality products. Flash-vacuum expansion (FVE) coupled with vacuum pulping is a new process that can meet these requirements. FVE was carried out at different holding times of steam blanching (30, 40, and 50 s/130 kPa) with or without the application of flash-vacuum expansion at 5 ± 1.2 kPa. The logarithmic reduction of microbial load and some quality indicators, such as β-carotene content and ascorbic acid (AA), were analyzed during the process and during storage to assess the shelf life of fruit purees. The total energy consumption of all subsystems was then assessed. The FVE process with 40 s steam blanching led to a microbial reduction of over 6 log CFU/g, increased yield and β- carotene content and preserved most of the AA content (4-12%). Based on the half-lives of the quality indicators, the shelf life of the purées was between 16 d (20 °C) and 90 d (4 °C). The energy consumption was estimated at approximately 0.30 kWh/kg of product. These results demonstrate that the FVE process, although it includes a heat treatment, allows a short exposure to heat of the whole fruits to obtain a high-quality puree with an adequate shelf life in a single step, with a relatively low equipment investment and moderate energy consumption.